Applying the International Classification of Functioning, Disability & Health A Team-Based/Project Based Course for Undergraduate Students - Schroder, Laurie (Open textbook library., 2021)
This text is a complete team-based and project-based learning course focused on the application of the World Health Organization’s International Classification of Functioning, Disability and Health (ICF) to unique groups of program clients and patients. It is designed to engage undergraduate students in exploration of the different facets of the ICF, in how the ICF differs from medical and social models because of these facets, and how each applies to, and ensures, an awareness of all of the ways in which health affects and is affected by peoples’ characteristics and environments. The text includes readings, digital links, readiness assurance elements, and guidelines for individual and team deliverables, but can also be used as a stand-alone text to provide a rich constructivist approach to understanding the structure of the ICF and how to use it for problem solving and decision-making with a patient/client population. It is the author’s intention that the text be used as suits the instructor, and modified to fit the pre-professional or paraprofessional healthcare students being taught, so while case study examples for rehabilitation are include, the text will lend itself to any patient or client group.